The giving tree - Silverstein, Shel (New York, N.Y. : Harper & Row, 1992)
A young boy grows to manhood and old age experiencing the love and generosity of a tree which gives to him without thought of return.
English version
Some copies may have a 50th anniversary sticker.
530
Accelerated Reader
Keywords: Trees -- Juvenile fiction